Cutaneous adverse events in children treated with vemurafenib for refractory BRAFV600E mutated Langerhans cell histiocytosis. Issue 9 (9th June 2021) - Tardieu, Mathilde; Néron, Amélie; Duvert‐Lehembre, Sophie; Amine Larabi, Islam; Barkaoui, Mohamed; Emile, Jean‐Francois; Seigneurin, Arnaud; Boralevi, Franck; Donadieu, Jean
Abstract: Background: The somatic BRAF V600E mutation occurs in 38–64% of pediatric cases of Langerhans cell histiocytosis (LCH). Vemurafenib (VMF), a BRAF inhibitor, was approved for refractory BRAF V600E mutated LCH. In adults, VMF causes frequent cutaneous adverse events (CAE) including skin tumors (squamous cell carcinomas, melanomas), but little is known in children. The objective of this study was to evaluate the frequency, clinical spectrum, and severity of CAEs in children treated with VMF for LCH. In addition, a correlation between CAE occurrence and VMF dose, residual plasma levels (RPLs), and efficacy was searched for. Procedure: Multicentric retrospective observational study including patients <18 years treated with VMF alone for refractory BRAF V600E mutated LCH in 13 countries between October 1, 2013 and December 31, 2018. Results: Fifty‐seven patients: 56% female, median age 2.1 years (0.2–14.6), median treatment duration 4.1 months (1.4–29.7). Forty‐one patients (72%) had at least one CAE: photosensitivity (40%), keratosis pilaris (32%), rash (26%), xerosis (21%), and neutrophilic panniculitis (16%). No skin tumor was observed. Five percent of CAEs were grade 3. None were grade 4 or led to permanent VMF discontinuation. Dose reduction was necessary for 12% of patients, temporary treatment discontinuation for 16%, none leading to loss of efficacy. VMF dose, median RPL, and efficacy were not correlated with CAE occurrence. Conclusions: At doses used for pediatric LCH, CAEs are frequent but rarely severe and have little impact on the continuation of treatment when managed appropriately. Regular dermatological follow‐up is essential to manage CAEs and screen for possible induced skin tumors.